Pyrithione Zn selectively inhibits hypoxia-inducible factor prolyl hydroxylase PHD3 - Na, Yu-Ran; Woo, Dustin J.; Kim, So Yeon; Yang, Eun Gyeong (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2016)
Increasing evidence emphasizes the role of the hypoxia-inducible factor (HIF) prolyl hydroxylase (PHD) isoforms in regulating non-HIF substrates, but isoform selective PHD inhibitors under physiological conditions have not yet been reported. Here we have identified pyrithione Zn (PZ) as a potent, isoform-selective PHD3 inhibitor. The IC50 value of PZ was determined as 0.98 mu M for PHD3, while it did not show any inhibitory activity toward full length and truncated PHD2 up to 1 mM. The selective efficacy of PZ was further demonstrated at the cellular level by observing inhibition of the PHD3-dependent DNA damage response pathway without stabilization of HIF-1 alpha. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: OXYGEN SENSOR; HIF-ALPHA; HIF-1-ALPHA; UBIQUITYLATION; METABOLISM; PROMOTES; SURVIVAL; FAMILY